2023
DOI: 10.1002/ptr.7869
|View full text |Cite
|
Sign up to set email alerts
|

Glycyrrhizae Radix et Rhizoma: The popular occurrence of herbal medicine applied in classical prescriptions

Abstract: Glycyrrhizae Radix et Rhizoma is a well-known herbal medicine with a wide range of pharmacological functions that has been used throughout Chinese history. This review presents a comprehensive introduction to this herb and its classical prescriptions. The article discusses the resources and distribution of species, methods of authentication and determination chemical composition, quality control of the original plants and herbal medicines, dosages use, common classical prescriptions, indications, and relevant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 223 publications
0
1
0
Order By: Relevance
“…Therefore, interventions targeting Treg cells have become the new strategy of many therapies for malignant tumors ( 106 , 107 ). Radix Glycyrrhizae is a commonly used traditional Chinese herbal medicine with a wide range of pharmacological functions throughout Chinese history, and the polysaccharide is a major active compound extracted from it, which is cytotoxic to cancer cells ( 108 , 109 ). An in vivo experimental study with H22 hepatocarcinoma-bearing BALB/c mice has shown that Radix Glycyrrhizae Polysaccharide could down-regulate the population of Treg cells and decrease the expression of Foxp3 mRNA and IL-10 mRNA in the lymph node.…”
Section: Experimental and Clinical Trials On Hcc Of Tcm Polysaccharid...mentioning
confidence: 99%
“…Therefore, interventions targeting Treg cells have become the new strategy of many therapies for malignant tumors ( 106 , 107 ). Radix Glycyrrhizae is a commonly used traditional Chinese herbal medicine with a wide range of pharmacological functions throughout Chinese history, and the polysaccharide is a major active compound extracted from it, which is cytotoxic to cancer cells ( 108 , 109 ). An in vivo experimental study with H22 hepatocarcinoma-bearing BALB/c mice has shown that Radix Glycyrrhizae Polysaccharide could down-regulate the population of Treg cells and decrease the expression of Foxp3 mRNA and IL-10 mRNA in the lymph node.…”
Section: Experimental and Clinical Trials On Hcc Of Tcm Polysaccharid...mentioning
confidence: 99%
“…The classical prescriptions of traditional Chinese medicine (TCM) have originated from the fixed combination of certain kinds of herbal medicines recorded in the ancient classics, which have been still widely used in East Asia and exhibited precise clinical efficacy, with obvious characteristics and advantages [ 1 ]. For a long time, some classic prescriptions have been developed into modern Chinese medicinal preparations through the optimization of preparation technology and drug development research [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%